Marathon Run II: Effects on Platelet Aggregation - Dimitriadou, C; Dessypris, A; Louizou, C; Mandalaki, T (Thrombosis and Haemostasis, 1977)
Platelet count and aggregation were assessed in 9 Finnish amateur runners aged 34 to 48, and one 65-year old taking part in a non-competitive marathon race (42.2 km).After the run the mean value of platelet count showed a very significant rise (p <0.001). The platelets were markedly more sensitive to both ADP and collagen-induced aggregation. A highly significant increase (p <0.001) was noted for both the intensity and velocity of platelet aggregation.The finding of platelet hyperaggregability after prolonged strenuous exercise even in trained subjects is discussed. It is concluded that a thorough medical examination of the haemostatic balance is recommended before a marathon race.